Elucidating new structural features of the triazole scaffold for the development of mPGES-1 inhibitors. Issue 1 (3rd October 2014) - Chini, Maria Giovanna; Ferroni, Claudia; Cantone, Vincenza; Dambruoso, Paolo; Varchi, Greta; Pepe, Antonella; Fischer, Katrin; Pergola, Carlo; Werz, Oliver; Bruno, Ines; Riccio, Raffaele; Bifulco, Giuseppe
Abstract : Halogen bonding as a new key interaction is useful for the design of novel triazole derivatives as mPGES-1 inhibitors. Abstract : We report a new potent revisited version of a triazole-based inhibitor obtained by structure-based drug design on the human mPGES-1 crystal structure. Moreover, we disclosed the substitution with a halogen atom at position 5 as a new key factor influencing the biological activity on the mPGES-1 enzyme.